Fair play in class and sports environment from the perspective of physical education and sports teacher - Cihad Güzel; İlyas Görgüt (Ozlem Book Center, 2024)
In this study, by focusing on the role of physical education and sports teachers in the development of fair play, it is aimed to raise awareness by determining teachers' practices, attitudes and knowledge levels about the concept. Phenomenological design was used in the study prepared with qualitative research method. A total of 21 physical education and sports teachers from 7 regions and 14 provincial participated in the sampling group of the study with the criterion sampling method, one of the purposeful sampling methods. Individual interviews were conducted with the teachers within the scope of semi-structured interview technique lasting an average of 30 minutes. Descriptive and content analysis methods were used to analyze the expressions. As a result of the analysis, Physical Education and Sports teachers express the concept of fair play in the lesson and sports environment as apologizing to the opponent by the athlete, extending a hand to the opponent as a result of any negative situation, consoling and congratulating him/her in case of success. Teachers use oral and visual expression methods in order to teach the concept to students and the reaction of the teachers to the rival team player who violated the rules during the competition varied according to various situations. In order to ensure a fair game understanding in sports environments, first of all, individuals competing on and off the field should have equal conditions in terms of facilities, materials, transportation and anthropometrics. In cases where professionalism is at the forefront, high level morale/motivation, result and target are the primary goals, while in cases where entertainment is at the forefront, fair play, healthy life and spending quality time are at the forefront.